2010
DOI: 10.1590/s0004-27302010000200018
|View full text |Cite
|
Sign up to set email alerts
|

The use of PTH in the treatment of osteoporosis

Abstract: SUMMARYAnabolic drugs have recently widened therapeutic options in osteoporosis treatment, as they influence processes associated with bone formation to a greater extent and earlier than bone reabsortion. They positively affect a number of skeletal properties besides bone density, as intermittent administration of parathyroid hormone (PTH) results in an increase in the number and activity of osteoblasts leading to an increase in bone mass and improvement in skeletal architecture at both the trabecular and cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…The anabolic effects of hPTH(1-34) are followed by excessive bone resorption. Increasing the dosage of PTH treatment is complicated, involving serious side effects of hypercalcemia and cortical porosity (26,27). Therefore, new development of PTH or PTHrp analogues with purer anabolic activity, such Abaloparatide, is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The anabolic effects of hPTH(1-34) are followed by excessive bone resorption. Increasing the dosage of PTH treatment is complicated, involving serious side effects of hypercalcemia and cortical porosity (26,27). Therefore, new development of PTH or PTHrp analogues with purer anabolic activity, such Abaloparatide, is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CaSR can activate extracellular signal-regulated kinase phosphorylation via protein kinase signaling pathways and maintain cell proliferation for a prolonged period [24, 25]. Parathyroid hormone is also a G protein-coupled receptor signaling protein and can regulate calcium balance by activating a series of physiological and biochemical reactions by specific receptors that are expressed on the surface of target organs and results in calcium effects [9, 10]. This study found that calcium fluorescence intensity in BMSCs was significantly higher in the experimental group (PTH treatment) than that found in the control group at the same culture times.…”
Section: Discussionmentioning
confidence: 99%
“…PTH is also a G protein-coupled receptor signaling protein with catabolic and anabolic functions. PTH can also regulate physiological calcium balance by activating a series of physiological and biochemical reactions by a specific receptor that is displayed on the surface of its target organ [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…[2] Intermittent low-dose treatment with recombinant human Parathyroid hormone (rhPTH 1-84) or recombinant human PTH peptide 1-34 (teriparatide) were used in the treatment of severe Osteoporosis, Daily injections of Parathyroid hormone (PTH), increase bone mass and reduce the incidence or prevention of Osteoporotic fractures in postmenopausal women, elderly men, and women with glucocorticoid-induced Osteoporosis. [3][4][5] Administration of PTH by this way result in an increase in the number and activity of Osteoblasts leading to an increase in bone mass and improvement in skeletal architecture at both trabecular and cortical bone. [3] Therefore, from the eighteenth of the last century till now, the attempts to produce the recombinant active parathyroid hormone with full length (84 amino acid) were recurred in verifying hosts, like Escherichia coli, yeast like Hansenula polymorph, Saccharomyces cerevisiae, Pichia pastoris, mammalian cells like Rat Pituitary Cells, Bombyx mori larvae and others using various recombinant vectors that carrying the gene coding for Parathyroid hormone.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Administration of PTH by this way result in an increase in the number and activity of Osteoblasts leading to an increase in bone mass and improvement in skeletal architecture at both trabecular and cortical bone. [3] Therefore, from the eighteenth of the last century till now, the attempts to produce the recombinant active parathyroid hormone with full length (84 amino acid) were recurred in verifying hosts, like Escherichia coli, yeast like Hansenula polymorph, Saccharomyces cerevisiae, Pichia pastoris, mammalian cells like Rat Pituitary Cells, Bombyx mori larvae and others using various recombinant vectors that carrying the gene coding for Parathyroid hormone. All these attempts aimed to get a large scale of hormone production with more suitable and simple extraction and purification method and that makes the other important part in the production of the recombinant protein is the processes of extraction and purification of that protein.…”
Section: Introductionmentioning
confidence: 99%